2019
DOI: 10.3389/fpsyg.2019.01647
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Learning, Bilingualism, and Dyslexia: Insights From a Study Assessing AGL With a Modified Simon Task

Abstract: This paper presents an experimental study investigating artificial grammar learning in monolingual and bilingual children, with and without dyslexia, using an original methodology. We administered a serial reaction time task, in the form of a modified Simon task, in which the sequence of the stimuli was manipulated according to the rules of a simple Lindenmayer grammar (more specifically, a Fibonacci grammar). By ensuring that the subjects focused on the correct response execution at the motor stage in presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 71 publications
(73 reference statements)
4
21
0
Order By: Relevance
“…In contrast to the traditional Simon task, our modified version, as in [53], presents two major changes, concerning (i) the sequence of blue and red squares and (ii) the occurrence of the incongruent trials.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast to the traditional Simon task, our modified version, as in [53], presents two major changes, concerning (i) the sequence of blue and red squares and (ii) the occurrence of the incongruent trials.…”
Section: Methodsmentioning
confidence: 99%
“…Some preliminary evidence for the robustness of implicit learning tasks featuring Fib has already been provided: in a pivotal research, [50,51] found that humans can discriminate between samples of true Fibonacci sequences and samples of foil sequences produced by means of n-gram substitution, up to substitution units of lengths 5 and 8; [52] found that participants were able to discriminate sequences of synthesised syllables following the Fibonacci grammar from random sequences with distributional properties matched to Fib. More recently, [53] found evidence of implicit learning in 10-year-old children (monolingual and bilingual children, with and without dyslexia), administering a modified Simon task developed following Fib's Three Laws. As in traditional Simon tasks, children were simply asked to press 1 (i.e.…”
Section: Employing the Fibonacci Grammar In Agl Studies: Preliminary mentioning
confidence: 99%
See 3 more Smart Citations